DECOLORIZATION OF DISTILLERY EFFLUENT WASTE BY MICROBIAL CONSORTIUM - Gauri Singh; Ashok Kumar Singh (Universitas Trisakti, 2020)
Aim: The effluent discharged from sugarcane molasses based distilleries causes environmental pollution due to its large volume and dark brown colour. The effluents also acifidys soils and causes harmful effects on agriculture crops. The objective of this work was the decolourization of molasses waste water from Doiwala sugar industry, Dehradun was done using different microbial consortiums. Methodology and Results: The microbial strains used in this study were obtained from IMTECH, Chandigarh. They were designated as A is E. coli, B is Pseudomonas aeruginosa, C is Staphylococcus aureus, D is Serritia odoriferae, E is Proteus vulgaris and F is Candida albicans. A total of six combinations were prepared using these strains i.e A+B, C+D, E+F, A+B+C, D+E+F and A+B+C+D+E+F. These consortiums were subjected to decolorization experiment of molasses waste water from Doiwala Sugar Factory, Dehradun, India at regular time interval by measuring the optical density. It was observed that at 7th day incubation in each case all consortiums showed maximum decolorization after which the percentage of decolorization was stable. It was also observed that the bacterial consortiums showed higher decolorization than the mixture of bacteria and fungi. Consortium C+D showed highest decolorization i.e. 89%. Conclusion, significance and impact study: it is recommended that industry should work with this consortium for decolorization of molasses containing wastewater to solve this environmental problem.